Association of Grip Strength with obesity & cortisol; Possible indicators of biological ageing - Mirza, Faizan; Fazal, Amaila; Shabbir, Khadija; Farooq, Hafsa; Ahmed , Sadaf (International Journal of Endorsing Health Science Research, 2020)
Background: Cortisol has a positive correlation with Obesity, which indicates a relation between obesity and cortisol. Furthermore, there are increased chances of demolished muscle strength up to two times with elevated levels of cortisol. Thus, the aim of the study was to assess the impact of increased cortisol levels on the grip strength and to determine that the grip strength is a possible indicator for accelerated biological ageing. Methodology: This cross-sectional, purposive sampling study was conducted in Karachi, Pakistan. Overall 412 were recruited to participate in the study, the data for age, gender, BMI, grip strength, and cortisol was collected from the participants. The age-wise correlates of hand grip strength were assessed using Multiple linear regression analysis and the mean decline in the grip strength with advancing age is displayed. Results: The mean Grip strength of the overall population was 30.75±14.35. It was observed that there was a negative significant correlation between the age and the grip strength (F = 3.57; r= -0.27; p=0.007) i.e. with increasing age a gradual decrease in the grip strength was observed. BMI (Obesity) was also significantly associated with grip strength (p=0.000). Moreover, females were more likely to have weak muscle strength as compared to males (p=0.000). However, no significant association was observed among the grip strength, socioeconomic status & longevity in any of the studied age groups (p>0.05). While a significant correlation was found between Grip strength and Obesity as well as between Obesity and Cortisol. Conclusion: Thus it can be concluded that obese individuals had increased chances of accelerated biological ageing due to an increase in cortisol, and a weakened grip strength is an indicator of it.